Neurologic findings caused by ossification of ligamentum flavum at the thoracolumbar junction. (4th May 2017) - Fujimoto, Kazuhiro; Kanchiku, Tsukasa; Imajo, Yasuaki; Suzuki, Hidenori; Yoshida, Yuichiro; Nishida, Norihiro; Funaba, Masahiro; Taguchi, Toshihiko
Abstract : Objective : To evaluate neurologic findings caused by a single ossification of ligamentum fravum (OLF) and identify the level of the lumbar segment of spinal cord. Design : Retrospective study. Methods : Subjects were 28 patients with a single OLF at T10-11 level (15 patients), T11-12 (11), and T12-L1 (2). The tip of the conus medullaris was assessed using computed tomographic myelography or magnetic resonance imaging. Neurologic evaluations were performed for patellar tendon reflex (PTR), sensory disturbance, and motor weakness. Results : The tip of the conus medullaris was located at the L1 vertebral body level. At the T10-11 level, all patients showed hyperreflexia of PTR. Sensory disturbance was observed for L1 dermatome and weakness of the iliopsoas was noted. At the T11-12 level, 8 of 11 patients didn't show hyperreflexia of PTR. Sensory disturbance was observed for L5 dermatome and weakness of the tibialis anterior was noted. At the T12-L1 level, all patients showed normal reflex of PTR, sensory disturbance of L5 dermatome, and weakness of the tibialis anterior. Conclusion : With regard to the relationship between PTR and OLF level, all patients at the T10-11 level showed involvement of the L3 segment of spinal cord proximally. On the other hand, most patients at the T11-12 level showed involvement of the L4 segment of spinal cord distally. From all neurologic findings, we confirmed the presence of the L4 segment of spinal cord from the lower third of T11 vertebral body to the T11-12 intervertebral disc level.